2021
DOI: 10.1158/0008-5472.can-21-0463
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA NIHCOLE Promotes Ligation Efficiency of DNA Double-Strand Breaks in Hepatocellular Carcinoma

Abstract: Long noncoding RNAs (lncRNA) are emerging as key players in cancer as parts of poorly understood molecular mechanisms. Here, we investigated lncRNAs that play a role in hepatocellular carcinoma (HCC) and identified NIHCOLE, a novel lncRNA induced in HCC with oncogenic potential and a role in the ligation efficiency of DNA double-stranded breaks (DSB). NIHCOLE expression was associated with poor prognosis and survival of HCC patients. Depletion of NIHCOLE from HCC cells led to impaired proliferation and increas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 57 publications
0
52
0
1
Order By: Relevance
“…A similar scaffolding role was suggested for NIHCOLE, whereby its interaction with Ku80 promotes the formation of multimeric NHEJ complexes to increase ligation efficiency [26]. However, in contrast to the role of LINP1 in long-range synapsis [27], NIHCOLE is implicated in short-range synapsis [26]. While long-range synaptic complexes can provide the initial tethering of the DNA ends, it is the short-range synaptic complex that catalyses their precise alignment and ligation [38], distinguishing the functions of the two scaffolding lncRNAs.…”
Section: Bs-drl1mentioning
confidence: 63%
See 3 more Smart Citations
“…A similar scaffolding role was suggested for NIHCOLE, whereby its interaction with Ku80 promotes the formation of multimeric NHEJ complexes to increase ligation efficiency [26]. However, in contrast to the role of LINP1 in long-range synapsis [27], NIHCOLE is implicated in short-range synapsis [26]. While long-range synaptic complexes can provide the initial tethering of the DNA ends, it is the short-range synaptic complex that catalyses their precise alignment and ligation [38], distinguishing the functions of the two scaffolding lncRNAs.…”
Section: Bs-drl1mentioning
confidence: 63%
“…Single-molecule assays utilising molecular forceps to imitate DSBs showed LINP1 to be even more effective than PAXX at bridging DNA ends [27], thus highlighting the increasing importance of studying RNA molecules as key drivers of DNA repair. A similar scaffolding role was suggested for NIHCOLE, whereby its interaction with Ku80 promotes the formation of multimeric NHEJ complexes to increase ligation efficiency [26]. However, in contrast to the role of LINP1 in long-range synapsis [27], NIHCOLE is implicated in short-range synapsis [26].…”
Section: Bs-drl1mentioning
confidence: 73%
See 2 more Smart Citations
“… 18 , 19 Unfried et al reported that the expression of NIHCOLE was related to the poor prognosis and survival of patients with HCC, and the inhibition of NIHCOLE expression in HCC cells may lead to limited cell proliferation and increased apoptosis rate through the accumulation of DNA damage. 20 Research by Peng et al showed that the expression of LINC00511 was higher in HCC tissues, and the mechanism study revealed that the invasion pseudopodia and exosomal secretion induced by LINC00511 were involved in tumor progression. 21 Yin et al found that LINC01133 expression in HCC tissues was elevated, and can predict the poor prognosis of HCC patients; in‐vitro studies showed that overexpression of LINC01133 can promote the proliferation and aggressive phenotype of HCC cells, and promote tumor growth and lung metastasis in vivo, while knockdown LINC01133 had the opposite effect.…”
Section: Discussionmentioning
confidence: 99%